Akuntabilitas Keuangan Desa dan Kesejahteraan Aparatur Desa dalam Pengelolaan Keuangan Desa - Yusuf Eko Nahuddin (University of Merdeka Malang, 2018)
The spirit of the Village building is the key word for the birth of Law No. 6 of 2014 concerning Villages, which must be realized with the efforts of professional village financial management to create community welfare and village apparatus as a juridical consequence of the enactment of Law No. 6 of 2014 concerning Villages relating to autonomous authority to manage village finance accountably for the achievement of village welfare which is a shared desire and noble ideals of the nation and also equally important is to improve the welfare of village apparatus to support these ideals so that they have no potential abuse of authority. Speaking about the village, it is inseparable from the position and authority of the village government, as the lowest government unit in Indonesia which still raises the pros and cons of the village government itself, one of the reasons is Regional Autonomy which lacks assertiveness about the task and authority of the village head , to manage its own finances, the finance obtained by the Village from the APBN (State Revenue and Expenditure Budget) is in the form of ADD (Village Fund Allocation).How to cite item: Nahuddin, Y. (2018). Akuntabilitas Keuangan Desa dan Kesejahteraan Aparatur Desa dalam Pengelolaan Keuangan Desa. Jurnal Cakrawala Hukum, 9(1), 107-116. doi:https://doi.org/10.26905/idjch.v9i1.2111